Post-Yugoslavia : new cultural and political perspectives - Abazović, Dino, 1972-; Velikonja, Mitja, 1965- (Palgrave Macmillan, 2014)
Designed as an interdisciplinary scholarly examination of the present-day identities and histories inside and outside the former Yugoslavia, this book explores relationships with the social, political, cultural and historical 'facts and fictions' that have marked the pre, peri and post-war dynamics of different parts of the region. Moreover, this innovative collection further studies the connections that the nations which comprise the former Yugoslavia have with the world and the actors and processes of transformation that are implicated in those relationships both within and beyond the region. The individual contributions address the social, political and symbolic processes by which competing histories and identities are continuously re-imagined and reconstructed, whether in the personal narratives of migrants, in ICTY courtrooms, in spaces of religious worship or in the offices of politicians. Collectively, the contributors show that while nationalism is still a relevant force other social dynamics and the narratives about them have a significant influence on individual countries as well as the region as a whole. The result is an extremely evocative volume that is an important read for students and scholars of political, social and cultural issues in the former Yugoslavia.